2000
DOI: 10.1126/science.290.5497.1779
|View full text |Cite
|
Sign up to set email alerts
|

Turning Blood into Brain: Cells Bearing Neuronal Antigens Generated in Vivo from Bone Marrow

Abstract: Bone marrow stem cells give rise to a variety of hematopoietic lineages and repopulate the blood throughout adult life. We show that, in a strain of mice incapable of developing cells of the myeloid and lymphoid lineages, transplanted adult bone marrow cells migrated into the brain and differentiated into cells that expressed neuron-specific antigens. These findings raise the possibility that bone marrow-derived cells may provide an alternative source of neurons in patients with neurodegenerative diseases or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
976
8
45

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,672 publications
(1,043 citation statements)
references
References 45 publications
14
976
8
45
Order By: Relevance
“…Previous in vivo studies have examined the differentiation of murine MSC. Transplantation of murine MSCs gave rise to neurons (8,29,35) and astrocytes (29). Two recent reports have shown that human MSCs could differentiate in vitro into neurons (49,57) and astrocytes (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vivo studies have examined the differentiation of murine MSC. Transplantation of murine MSCs gave rise to neurons (8,29,35) and astrocytes (29). Two recent reports have shown that human MSCs could differentiate in vitro into neurons (49,57) and astrocytes (49).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow stromal cells or mesenchymal stem cells (MSCs) not only give rise to mesodermal lineage cells such as osteoblasts, chondrocytes, adipocytes, and muscle cells (4,13,29,55,33), but also adopt neuroectodermal cell fate. It has been shown that donor-derived neurons and astrocytes are found in host rodent brain following transplantation of rodent bone marrow (8,14,29,35). However, it is not known if transplantation of MSCs into the brain can be beneficial in treating neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…These observations were mainly explained by the hypothesis that HSC are "plastic" and, thus, could trans-dedifferentiate into stem cells committed for various organs and tissues (Mezey et al, 2000;Corti et al, 2002b). This phenomenon to occur requires (1) a parallel switch of commitment for HSC in the compartment of stem cells or (2) alternatively, as postulated, a step back in the differentiation process from compartment of HSC with their dedifferentation into multipotent (one germ layercommitted) or even pluripotent (three germ layer-committed) stem cells.…”
Section: Bm-derived Stem Cells and Tissue/organ Regeneration: Evidencmentioning
confidence: 99%
“…Ongoing efforts in regenerative medicine have focused on this regeneration dilemma when using bone marrow as a source of cells that facilitate repair of injured organs without causing detrimental tissue reactions. Since it was shown that bone marrowderived cells can give rise to myocytes (Ferrari et al, 1998), hepatocytes (Petersen et al, 1999), endothelial and myocardial cells (Lin et al, 2000;Orlic et al, 2001a), neuronal and glial cells (Brazelton et al, 2000;Mezey et al, 2000), and a number of other cell types (Krause et al, 2001), bone marrow-derived cells arte currently the preferred cell type used in regenerative medicine. A number of problems with these studies, including the lack of functional characterization of "switched cells," the mixed population of utilized donor cells used, and cell fusion, have been largely ignored.…”
Section: Organ Regeneration and Repairmentioning
confidence: 99%